2012
DOI: 10.1371/journal.pone.0043608
|View full text |Cite
|
Sign up to set email alerts
|

A New Zearalenone Biodegradation Strategy Using Non-Pathogenic Rhodococcus pyridinivorans K408 Strain

Abstract: Zearalenone (hereafter referred to as ZEA) is a nonsteroidal estrogenic mycotoxin produced by several Fusarium spp. on cereal grains. ZEA is one of the most hazardous natural endocrine disrupting chemicals (EDC) which induces hyper estrogenic responses in mammals. This can result in reproductive disorders in farm animals as well as in humans. Consequently, detoxification strategies for contaminated crops are crucial for food safety. In this study we have developed a bacterial based detoxification system using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 50 publications
(58 reference statements)
0
45
0
1
Order By: Relevance
“…For instance, there are some reports about Mycobacterium fluoranthenivorans, Rhodococcus erythropolis and other microbes related to their potentials of aflatoxin degradation (Teniola et al, 2005;Krifaton et al, 2011;Cserháti et al, 2013). Other studies indicate that ZEA can be degraded by Pseudomonas sp., Rhodococcus pyridinivorans and S. Cerevisiae (Altalhi, 2007;Kriszt et al, 2012;Gupta et al, 2012). Liu et al (1998) demonstrated that aflatoxin detoxifizyme obtained from Armillariella tabescens showed AFB 1 detoxification activities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there are some reports about Mycobacterium fluoranthenivorans, Rhodococcus erythropolis and other microbes related to their potentials of aflatoxin degradation (Teniola et al, 2005;Krifaton et al, 2011;Cserháti et al, 2013). Other studies indicate that ZEA can be degraded by Pseudomonas sp., Rhodococcus pyridinivorans and S. Cerevisiae (Altalhi, 2007;Kriszt et al, 2012;Gupta et al, 2012). Liu et al (1998) demonstrated that aflatoxin detoxifizyme obtained from Armillariella tabescens showed AFB 1 detoxification activities.…”
Section: Introductionmentioning
confidence: 99%
“…AFB1-degrading bacteria may be aromatic ringdegrading microbes (Cserh ati et al, 2013;Krifaton et al, 2011). ZON degradation was reported to be successful using several Rhizopus strains (Varga et al, 2005), the Pseudomonas putida ZEA-1 strain (Altalhi, 2007), the Rhodococcus pyridinivorans (K408) strain (Kriszt et al, 2012) and some Streptomyces and Rhodococcus strains .…”
Section: Introductionmentioning
confidence: 99%
“…Certain strains of rhodococci were shown to degrade mycotoxins: zearalenone (Kriszt et al 2012), or aflatoxin B 1 (Alberts et al 2006).…”
Section: Introductionmentioning
confidence: 99%